Veronica Cymbalaria (Plantaginaceae): A New Species For The Exotic Flora Of Chile - Cisternas, Mauricio A.; Cádiz Véliz, Arón; Novoa, Patricio; Macaya Berti, Jorge (My University, 2023)
Background and aims: Botanic gardens play a fundamental role in conservation due to the maintenance of seed and live plant collections. However, the exchange of ornamental plant seeds between botanic gardens can facilitate the entry of seeds of alien species with invasive potential. In 2018, during a visit to the collections of the National Botanical Garden (Chile), we discovered populations of an herb of the genus Verónica (Plantaginaceae). The aim of this paper is to report for the first time the presence of Verónica cymbalaria as a new exotic feral species for the flora of Chile. M&M: Live material was studied and compared with the original description of the species. The collected material was deposited in the herbarium of the National Botanical Garden (JBN). Results: Verónica cymbalaria, which grows abundantly in and around the biological collections of the National Botanical Garden, is described. Images of the species, a map of the site of occurrence and a key to distinguish Verónica species growing in Chile are included. Conclusions: Verónica cymbalaria is reported for the first time for the flora of Chile. The distribution range of this alien species is extended to southern America. The genus Verónica is represented by ten allochthonous species in Chile.
Keywords: Alien plants; Central Chile; Flora of Chile; Taxonomy; Valparaíso Region; Weeds